Binocular interactions underlying the classic optomotor responses of flying flies - Duistermars, Brian J.; Care, Rachel A.; Frye, Mark A. (Frontiers in Behavioral Neuroscience, 2012)
In response to imposed course deviations, the fast optomotor reactions of animals reduce motion blur and facilitate the maintenance of stable body posture. In flies, the monocular front-to-back (progressive) and back-to-front (regressive) visual motion components generated by horizontal rotation are selectively encoded, respectively, by homo and heterolateral motion sensitive circuits in the third optic ganglion, the lobula plate. To investigate the strength of such inter-ocular interactions and their role in compensatory sensory-motor transformations, we utilize a virtual reality flight simulator to record optomotor reactions by tethered flying flies in response to imposed binocular and monocular visual rotation. With stimulus parameters generating large contrast insensitive optomotor responses to binocular rotation, we find that responses to monocular progressive motion are larger than those to panoramic rotation but contrast sensitive. Conversely, responses to monocular regressive motion are slower than those to rotation and peak at the lowest tested contrast. Together our results suggest that contrast insensitive optomotor responses to binocular rotation result from the dynamic interplay of contralateral inhibitory as well as excitatory circuit interactions and serve to maintain a stable optomotor equilibrium across a range of visual contrasts.